Diverse Internal Symbiont Community in the Endosymbiotic Foraminifera Pararotalia calcariformata: Implications for Symbiont Shuffling Under Thermal Stress - Schmidt, Christiane; Morard, Raphael; Romero, Oscar; Kucera, Michal (Frontiers in Microbiology, 2018)
Many shallow-water tropical and subtropical foraminifera engage in photosymbiosis with eukaryotic microalgae. Some of these foraminifera appear to harbour a diverse consortium of endosymbiotic algae within a single host. Such apparent ability to contain different symbionts could facilitate change in symbiont community composition (symbiont shuffling) and mediate the ecological success of the group in a changing environment. However, the discovery of the intra-individual symbiont diversity was thus far based on symbiont culturing, which provides strong constraints on the vitality of the identified algae but provides poor constraints on their initial abundance and thus functional relevance to the host. Here we analyze the algal symbiont diversity in Pararotalia calcariformata, a benthic foraminifera sampled at four stations, inside and outside of a thermal plume in the eastern Mediterranean coast of Israel. This species has recently invaded the Mediterranean, is unusually thermally tolerant and was described previously to host at least one different diatom symbiont than other symbiont-bearing foraminifera. Our results using genotyping and isolation of algae in culture medium, confirm multiple associations with different diatom species within the same individual. Both methods revealed spatially consistent symbiont associations and identified the most common symbiont as a pelagic diatom Minutocellus polymorphus. In one case, an alternative dominant symbiont, the diatom Navicula sp., was detected by genotyping. This diatom was the third most abundant species identified using standard algae culturing method. This method further revealed a spatially consistent pattern in symbiont diversity of a total of seventeen identified diatom species, across the studied localities. Collectively, these results indicate that P. calcariformata hosts a diverse consortium of diatom endosymbionts, where different members can become numerically dominant and thus functionally relevant in a changing environment.